Solution theory model for thermophysical properties of refrigerant/lubricant mixtures (2009)
ABSTRACT: A general model for predicting the thermos physical properties of refrigerant/lubricant mixtures has been developed based on applicable theory for the excess Gibbs energy of non-ideal solutions. In our approach, flexible thermodynamic forms are chosen to describe the properties of both the gas and liquid phases of refrigerant/lubricant mixtures. After an extensive study of models for describing non ideal liquid effects, the Wohl [3]-suffix equations, which have been extensively used in the analysis of hydro-carbon mixtures, have been developed into a general form applicable to mixtures where one component is a polyolester or alkylbenzene lubricant. We have developed anon ideal solution computer code, based on the Wohl model that predicts dew point orbubble point conditions over a wide range of composition and temperature and includes the calculation of the enthalpy and entropy of refrigerant/lubricant mixtures. Our present analysis includes the thermodynamic properties of an ideal solution mixture and the corrections due to non-ideal solution behavior. These non-ideal solution corrections are based on analysis of the excess Gibbs energy of the mixture. We find that these non-ideal solution corrections are small (\4%) for most refrigerant/lubricant mixtures, except at very low temperatures.